(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study analyzes and contrasts the eco-critical strategies used in the poetry of the two contemporary Indian poets, Mamang Dai and Temsula Ao who belong to the Northeast Region in India. It examines how the poets describe the natural environment and the connection via language, images and ideas. The paper contends that although their poems are eco-critical, their methods vary in scope, diction and cultural setting. It also highlights how these two poets showcase environment in their lasting pieces through a comparative analysis and emphasizes on the value of eco-literature in addressing environmental concerns